IMPELEMENTASI MODEL PEMBELAJARAN ADVANCE ORGANIZER DALAM PENDIDIKAN AGAMA ISLAM - Rika Sartika; Mukarromah; Nurdin, Syafruddin (Jurnal Pendidikan Islam, 2023)
The existing teaching and learning process determines success in achieving educational goals, as well as in Islamic education. The process of such change is influenced by two factors, among them internal factors and external factors. Internal factors include physiological aspects and psychological aspects and external factors, one of which is the learning model. One of the good learning models that can be applied to the teaching and learning process is the advanced organizer learning model. This study aims to explore the specifics of the advanced organizer learning model that can also be used in learning Islamic education. This research is literature research, which is analyzed using the method of description, interpretation, and data analysis. The discussion in this study includes the understanding of the advanced organizer learning model, its forms and objectives, steps, and advantages and disadvantages. The results showed that this model is a learning model that emphasizes the importance of strengthening students' initial knowledge as a preparation effort to receive new material. There are two forms, namely: Expository Advance Organizer and Comparative Advance Organizer. The model has four objectives, and three Step phases. This model also has some advantages as well as disadvantages.